Association between single and mixed exposure to polycyclic aromatic hydrocarbons and biological aging - Fu, Zuqiang; Zhang, Xianli; Zhong, Chunyu; Gao, Zhe; Yan, Qing (Frontiers in Public Health, 2024)
Background: Aging is one of the important public health issues. Previous studies on the factors affecting aging focused on genetics and lifestyle, but the research on polycyclic aromatic hydrocarbon (PAH) and aging is still unclear.: This study utilized data from the National Health and Nutrition Examination Survey (NHANES) 2003-2010. A total of 8,100 participants was used to construct the by using recent advanced algorithms, Klemera and Doubal method (KDM) and Mahala Nobis distance. Two biological aging indexes, recorded as KDM-BA acceleration and PhenoAge acceleration, were performed to investigate the relationship of single-PAH and biological age with multiple linear regression, and weighted quantile sum (WQS) model was constructed to explore the mixed effects of PAHs on the biological age. Then, we constructed restricted cubic spline (RCS) model to assess the non-linear relationship of PAHs and biological age. Results: PAHs exposure were associated with PhenoAge acceleration. Each unit increment in log10-transformed level of 1-napthol, 2-napthol and 2-fluorene was associated with a 0.173-(95% CI: 0.085, 0.261), 0.310-(95% CI: 0.182, 0.438) and 0.454-(95% CI: 0.309, 0.598) increase in PhenoAge acceleration, respectively (All corrected P <0.05). The urinary PAHs mixture was relevant to KDM-BA acceleration (β = 0.13, 95% CI:0, 0.26, P=0.048) and PhenoAge acceleration (β = 0.59, 95% CI: 0.47, 0.70, P<0.001) and 2-napthol had the highest weight in the WQS regression. The RCS analyses observed a non-linear association between 2-napthol and 2-fluorene with KDM-BA acceleration (All P <0.05) as well as a non-linear association between 1-napthol, 2-napthol, 3-fluorene, 2-fluorene, and 1-pyrene with PhenoAge acceleration (All P <0.05). Conclusions: PAH mixed exposure is associated with increased aging, with 2-napthol being a key component of PAH causing aging. These findings identified risk factors for aging.